Dentist in mission indradhanush: A target-to-target India's unvaccinated children - Ravneet Malhi (Dentistry and Medical Research, 2017)
Introduction: Immunization is one of the most effective, safest, and efficient public health interventions and was first introduced in India in 1978. While the impact of immunization on childhood morbidity and mortality has been great, its full potential has yet to be reached. Objective: This study aimed to assess the level of knowledge, attitude, and practice (KAP) among local community and dental students studying in dental college toward child immunization. Methodology: In this cross-sectional, questionnaire-based study, data were collected from patients attending the outpatient section of pediatric department of four private hospitals and dental students who are studying in a dental college. Further, data were analyzed using Statistical Package for Social Sciences (SPSS) 18.0, as well as descriptive and analytical tests, including mean, standard deviation, and Chi-square test. Results: Impaired KAP regarding immunization were observed among the parents and significant higher knowledge was assessed among dental students. A significant relationship was observed between level of education and awareness of immunization and between age and attitude to immunization (P < 0.05). Conclusion: Immunization has delivered excellent results in reducing morbidity and mortality from childhood infections in the last 50 years, but still there is a room for improvement.